Contrast Media: Are There Differences in Nephrotoxicity among Contrast Media? - Solomon, Richard (Hindawi Publishing Corporation, 2014)
Iodinated contrast agents are usually classified based upon their osmolality—high, low, and isosmolar. Iodinated contrast agents are also nephrotoxic in some but not all patients resulting in loss of glomerular filtration rate. Over the past 30 years, nephrotoxicity has been linked to osmolality although the precise mechanism underlying such a link has been elusive. Improvements in our understanding of the pathogenesis of nephrotoxicity and prospective randomized clinical trials have attempted to further explore the relationship between osmolality and nephrotoxicity. In this review, the basis for our current understanding that there are little if any differences in nephrotoxic potential between low and isosmolar contrast media will be detailed using data from clinical studies.